Low-resistivity carbon composite phosphoric acid and sodium ferric pyrophosphate positive electrode material, preparation method thereof and application of positive electrode material in sodium-ion battery

By introducing a catalyst into the composite sodium iron phosphate positive electrode material for low temperature catalysis, the graphitization degree of the carbon coating is improved, and the problem of low conductivity of existing materials is solved, and higher conductivity and more stable cycling performance are achieved.

CN119637836AInactive Publication Date: 2025-03-18SHANGHAI PUNA ENERGY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411814576.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The current composite sodium iron phosphate positive electrode material has poor conductivity and an inorganic carbon source needs to be added to improve conductivity. However, the inorganic carbon source is costly and has poor dispersion in the aqueous slurry, resulting in low sample purity.

Method used

The catalyst is introduced for low temperature catalysis, and the graphitization degree of coated carbon is improved, thereby improving the conductivity of the composite sodium iron phosphate positive electrode material. This method uses an iron-based catalyst as the graphitization catalyst, and the proportion of the catalyst is appropriately increased in the solid phase sintering technology to improve the graphitization degree of carbon materials.

Benefits of technology

It effectively reduces the powder resistivity of the positive electrode material, improves its conductivity, and reduces the generation of miscellaneous elements and magnetic foreign matters, and improves the long cycle stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119637836A_ABST
    Figure CN119637836A_ABST
Patent Text Reader

Abstract

The invention discloses a low-resistivity carbon composite ferric phosphate sodium pyrophosphate positive electrode material, a preparation method thereof and an application of the positive electrode material in a sodium ion battery. The preparation method comprises the following steps: (1) weighing an iron source, a sodium source, a phosphorus source and the like, and carrying out raw material proportioning according to the element proportion of the carbon composite ferric phosphate sodium material Na4Fe3 (PO4) 2P2O7 (at) C; (2) sequentially adding the raw materials into a stirring tank filled with deionized water, and stirring until the raw materials are completely dispersed and dissolved without agglomeration to obtain slurry; (3) carrying out spray granulation on the slurry by utilizing spray drying; dry precursor powder is obtained; (4) carrying out sintering reaction on the precursor powder under the protection of inert gas to obtain carbon composite sodium ferric phosphate positive electrode material particles; and (5) crushing and grading the composite sodium iron phosphate positive electrode material particles to obtain the composite sodium iron phosphate positive electrode material. The iron-based catalyst is adopted at the raw material proportioning end, so that the graphitization degree of the coated carbon material is properly increased, and the conductivity of the positive electrode material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of sodium ion batteries, and in particular to a preparation method and application of a low-resistivity carbon composite phosphate sodium iron pyrophosphate positive electrode material. Background Art

[0002] Sodium-ion batteries have attracted widespread attention due to their low cost, high safety, and excellent wide temperature performance. Among them, the composite sodium iron phosphate positive electrode material of sodium-ion batteries has become one of the most industrially promising positive electrode material technology routes due to its long cycle stability, high thermal stability, and high safety. The composite sodium iron phosphate positive electrode material belongs to the positive electrode material of the polyanion system, and its own electrical conductivity is poor; it is necessary to add a carbon source for carbon coating and compounding to improve its own electrical conductivity. However, due to its own low generation temperature, the degree of graphitization of the organic carbon source during the carbonization process is low, the carbon layer arrangement is relatively chaotic, and the conductivity improved by the residual carbon is limited, so it is often necessary to add inorganic carbon sources such as graphene, carbon nanotubes, etc. to improve the electrical conductivity. In the prior art CN116885150A, a composite carbon source-coated composite sodium iron phosphate positive electrode material and a preparation method, an inorganic carbon source and an organic carbon source are added as a composite carbon source. However, since the cost of the inorganic carbon source is relatively high and the inorganic carbon sources are all hydrophobic raw materials that are difficult to disperse in the aqueous slurry, the dispersibility of the slurry is poor, and the phase purity of the solid phase synthesized sample is low. Summary of the invention

[0003] To solve this problem, the applicant introduced a catalyst to increase the graphitization degree of the coated carbon at low temperature, thereby increasing the resistivity of the composite sodium iron phosphate positive electrode material. The specific technical solution of the present invention is as follows:

[0004] The invention discloses a method for preparing a low-resistivity carbon composite phosphate sodium iron pyrophosphate positive electrode material, comprising the following steps:

[0005] Step (1): weighing an iron source, a sodium source, a phosphorus source, a dispersant, an organic carbon source and a catalyst, wherein the iron source, the sodium source and the phosphorus source are mixed according to the element ratio of the carbon composite sodium iron phosphate material Na4Fe3PO4P2O7@C (@C indicates carbon coating);

[0006] Step (2): adding the raw materials in sequence into a stirring tank filled with deionized water, stirring until the raw materials are completely dispersed and dissolved without agglomeration, thereby obtaining a slurry;

[0007] Step (3): spray granulating the slurry by spray drying to obtain a dry precursor powder;

[0008] Step (4): sintering the precursor powder under the protection of an inert gas to obtain carbon composite sodium iron phosphate positive electrode material particles;

[0009] Step (5): crushing and classifying the composite sodium iron phosphate positive electrode material particles to obtain a composite sodium iron phosphate positive electrode material.

[0010] Furthermore, in the step (1), the ratio of the dispersant to the organic carbon source is 1:1, accounting for 5% to 10% by mass; the catalyst as a part of the iron source has a molar ratio of 10% to 50% in the iron source.

[0011] Furthermore, in the step (2), the solid content of the slurry is 10-60 wt %, the pH is 3-7, and the stirring time is 0.5-3 h.

[0012] Furthermore, in step (3), the inlet air temperature of the spray drying is 160-250°C; and the outlet air temperature is 75-115°C.

[0013] Furthermore, in the step (4), the sintering temperature of the sintering reaction is 440° C. to 600° C., the holding time is 3 to 10 hours, and the heating rate is 2 to 10° C. / min.

[0014] Furthermore, in step 4, the carbon content in the positive electrode material is 1% to 3%, wherein the inert gas includes one of N2 and Ar2.

[0015] Furthermore, in the step (5), the crushed particle size D50 of the crushed and classified material is 1 to 5 μm; the powder resistivity of the composite sodium iron phosphate positive electrode material is 10 Ω / cm 3 ~100000Ω / cm 3 ; Graphitization degree of carbon coating layer I D / I G It is 2.0~3.5.

[0016] Further, the iron source includes one or more of ferric phosphate, ferrous oxalate, and ferric nitrate;

[0017] The sodium source includes one or more of sodium oxalate, sodium phosphate, sodium pyrophosphate, sodium formate, sodium acetate, and sodium carbonate;

[0018] The phosphorus source includes one or more of phosphoric acid, ammonium phosphate, and pyrophosphoric acid;

[0019] The carbon source includes one or more of glucose, sucrose, citric acid, malic acid, phenolic resin, and gluconic acid;

[0020] The dispersant includes one or more of polyethylene glycol and polyvinyl alcohol;

[0021] The catalyst includes one or more of FeO, Fe2O3, Fe3O4, FeCl3, Fe(OH)3, Fe powder and the like.

[0022] The invention also discloses a composite sodium iron phosphate positive electrode material, which is prepared by the above-mentioned preparation method.

[0023] The present invention also discloses a method for preparing a sodium ion battery positive electrode sheet, comprising the following steps:

[0024] Step (1): mixing the composite sodium iron phosphate positive electrode material of claim 9 with a conductive agent and an adhesive in a mass ratio of 0.95:0.25:0.25 to prepare a mixed slurry;

[0025] Step (2): stirring the mixed slurry evenly, coating the mixed slurry evenly on a carbon-coated aluminum foil, and performing vacuum drying in an oven to obtain a positive electrode material for a battery;

[0026] Step (3), slicing the battery positive electrode material, evenly cutting it into circular electrode sheets, and performing secondary drying on the circular electrode sheets to obtain a sodium ion battery positive electrode sheet.

[0027] Furthermore, the conductive agent is one or more of conductive carbon black, acetylene, carbon nanotubes, and conductive graphite; and the solvent for making the mixed slurry is nitrogen methyl pyrrolidone.

[0028] Furthermore, the stirring time of the mixed slurry in step (2) is 2 hours, and the drying time is 3 hours; and the secondary drying time in step (3) is 2 hours.

[0029] Furthermore, the diameter of the circular electrode sheet is 14 mm, and the surface density (surface loading of the electrode sheet) is 15-20 mg / cm 2 .

[0030] The present invention also discloses a button battery, comprising the following materials;

[0031] The composite sodium iron phosphate positive electrode sheet prepared by the aforementioned method, the negative electrode is metallic sodium, the separator is GF / C, and the electrolyte is NaPF6 dissolved in ethylene carbonate (EC) + dimethyl carbonate (DMC).

[0032] Furthermore, the electrolyte is 1 mol; and the electrode shell model of the button battery is CR2016.

[0033] The present invention utilizes an iron-based catalyst as a graphitization catalyst for coated carbon, and at the same time participates in the synthesis of a composite sodium iron phosphate positive electrode material as an iron source, thereby improving the conductivity of the composite sodium iron phosphate positive electrode material. Its beneficial effects are: 1) The technical solution of the present invention adopts solid-phase sintering technology, and an iron-based catalyst is used at the raw material ratio end to appropriately increase the graphitization degree of the coated carbon material, thereby achieving the effect of increasing the conductivity of the composite sodium iron phosphate positive electrode material and reducing the powder resistivity of the positive electrode material. Excellent rate performance is shown in the electrochemical method. 2) Due to the use of an iron-based catalyst, it can also participate in the formation of the sodium iron pyrophosphate phase during the catalytic process, thereby reducing the formation of impurity elements and reducing the formation of magnetic foreign matter. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The drawings described herein are used to provide further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0035] Figure 1 The charge and discharge curves of the carbon composite sodium iron phosphate sample prepared in Example 1 at different current rates;

[0036] Figure 2 1C cycle diagram of the carbon composite sodium iron phosphate sample prepared in Example 1;

[0037] Figure 3 : This is a SEM micrograph of the carbon composite sodium iron phosphate sample prepared in Example 1. DETAILED DESCRIPTION

[0038] In order to more clearly illustrate the overall concept of the present application, a detailed description is given below in an illustrative manner in conjunction with the accompanying drawings.

[0039] Example 1: Step 1: Raw materials: weigh 2 mol of ferric phosphate, 1 mol of disodium hydrogen phosphate, 1 mol of sodium carbonate, 0.5 mol of Fe2O3, polyethylene glycol as the dispersant, and glucose as the carbon source, all accounting for 5 wt%.

[0040] Step 2: Add the weighed raw materials in step 1 into a stirring tank filled with deionized water in sequence, stir for 1 hour until the raw materials are completely dispersed and dissolved without agglomeration, transfer to a sand mill, and perform sand milling to obtain a slurry. The slurry pH is 7, and the slurry particle size D50 is 0.15 μm.

[0041] Step 3: spray granulate the slurry in step 2 by spray drying to obtain dry precursor powder, wherein the inlet air temperature of the spray drying is 230°C; and the outlet temperature is 112°C.

[0042] Step 4: The precursor powder in step 3 is subjected to sintering reaction under the protection of inert gas, the sintering temperature is 500°C, the holding time is 6 hours, and the heating rate is 3°C / min, to obtain carbon composite sodium iron phosphate positive electrode material particles. The carbon content in the positive electrode material particles is 2.2%, wherein the inert gas is N2.

[0043] Step 5: crush and classify the composite sodium iron phosphate positive electrode material particles obtained in step 4, wherein the crushed particle size D50 is 3 μm, to obtain the final composite sodium iron phosphate positive electrode material. The powder resistivity of the positive electrode material is 5000 Ω / cm 3 ; Raman test peak area ratio I D / I G =2.5.

[0044] After assembling it into a button-type half-cell, electrochemical tests showed that the reversible gram capacity at 0.2C was 102 mAh / g, the ICE was 90%, the reversible gram capacity at 1C was 100 mAh / g, and the 1C cycle stability for 200 cycles was greater than 99.5%.

[0045] Example 2: Step 1: Raw materials: weigh 2 mol of ferric phosphate, 1 mol of disodium hydrogen phosphate, 1 mol of sodium carbonate, 1 mol of FeO, polyethylene glycol as the dispersant, and glucose as the carbon source, all accounting for 5 wt%.

[0046] Step 2: Add the weighed raw materials in step 1 into a stirring tank filled with deionized water in sequence, stir for 1 hour until the raw materials are completely dispersed and dissolved without agglomeration, transfer to a sand mill, and perform sand milling to obtain a slurry. The slurry pH is 7, and the slurry particle size D50 is 0.15 μm.

[0047] Step 3: spray granulate the slurry in step 2 by spray drying to obtain dry precursor powder, wherein the inlet air temperature of the spray drying is 230°C; and the outlet temperature is 112°C.

[0048] Step 4: The precursor powder in step 3 is subjected to sintering reaction under the protection of inert gas, the sintering temperature is 500°C, the holding time is 6 hours, and the heating rate is 3°C / min, to obtain carbon composite sodium iron phosphate positive electrode material particles. The carbon content in the positive electrode material is 2.2%, wherein the inert gas is N2.

[0049] Step 5: crush and classify the composite sodium iron phosphate positive electrode material particles obtained in step 4, wherein the crushed particle size D50 is 3 μm, to obtain the final composite sodium iron phosphate positive electrode material. The powder resistivity of the positive electrode material is 30000 Ω / cm 3 ; Raman test peak area ratio I D / I G =2.8.

[0050] After assembling it into a button-type half-cell, electrochemical tests showed that the reversible gram capacity at 0.2C was 100 mAh / g, the ICE was 88%, the reversible gram capacity at 1C was 97.5 mAh / g, and the 1C cycle stability for 200 cycles was greater than 99%.

[0051] Example 3: Step 1: Raw materials: weigh 2 mol of ferric phosphate, 1 mol of disodium hydrogen phosphate, 1 mol of sodium carbonate, 0.33 mol of Fe3O4, polyethylene glycol as the dispersant, and glucose as the carbon source, all accounting for 5 wt%.

[0052] Step 2: Add the weighed raw materials in step 1 into a stirring tank filled with deionized water in sequence, stir for 1 hour until the raw materials are completely dispersed and dissolved without agglomeration, transfer to a sand mill, and perform sand milling to obtain a slurry. The slurry pH is 7, and the slurry particle size D50 is 0.15 μm.

[0053] Step 3: spray granulate the slurry in step 2 by spray drying to obtain dry precursor powder, wherein the inlet air temperature of the spray drying is 230°C; and the outlet temperature is 112°C.

[0054] Step 4: The precursor powder in step 3 is subjected to sintering reaction under the protection of inert gas, the sintering temperature is 500°C, the holding time is 6 hours, and the heating rate is 3°C / min, to obtain carbon composite sodium iron phosphate positive electrode material particles. The carbon content in the positive electrode material particles is 2.2%, wherein the inert gas is N2.

[0055] Step 5: crush and classify the composite sodium iron phosphate positive electrode material particles obtained in step 4, wherein the crushed particle size D50 is 3 μm, to obtain the final composite sodium iron phosphate positive electrode material. The powder resistivity of the positive electrode material is 15000 Ω / cm 3 . Raman test peak area ratio I D / I G =2.7.

[0056] After assembling it into a button-type half-cell, electrochemical tests showed that the reversible gram capacity at 0.2C was 101 mAh / g, the ICE was 89%, the reversible gram capacity at 1C was 98.5 mAh / g, and the 1C cycle stability for 200 cycles was greater than 99%.

[0057] Example 4: Step 1: Raw materials: weigh 2 moL of ferric phosphate, 1 moL of disodium hydrogen phosphate, 1 moL of sodium carbonate, 1 moL of FeCl3, polyethylene glycol as the dispersant, and glucose as the carbon source, all of which account for 5wt%.

[0058] Step 2: Add the weighed raw materials in step 1 into a stirring tank filled with deionized water in sequence, stir for 1 hour until the raw materials are completely dispersed and dissolved without agglomeration, transfer to a sand mill, and perform sand milling to obtain a slurry. The slurry pH is 7, and the slurry particle size D50 is 0.15 μm.

[0059] Step 3: spray granulate the slurry in step 2 by spray drying to obtain dry precursor powder, wherein the inlet air temperature of the spray drying is 230°C; and the outlet temperature is 112°C.

[0060] Step 4: The precursor powder in step 3 is subjected to sintering reaction under the protection of inert gas, the sintering temperature is 500°C, the holding time is 6 hours, and the heating rate is 3°C / min, to obtain carbon composite sodium iron phosphate positive electrode material particles. The carbon content in the positive electrode material particles is 2.2%, wherein the inert gas is N2.

[0061] Step 5: crush and classify the composite sodium iron phosphate positive electrode material particles obtained in step 4, wherein the crushed particle size D50 is 3 μm, to obtain the final composite sodium iron phosphate positive electrode material. The powder resistivity of the positive electrode material is 55000 Ω / cm 3 ; Raman test peak area ratio I D / I G =2.9.

[0062] After assembling it into a button-type half-cell, electrochemical tests showed that the reversible capacity at 0.2C was 100 mAh / g, the ICE was 89%, the reversible capacity at 1C was 96 mAh / g, and the 1C cycle stability for 200 cycles was greater than 99%.

[0063] Comparative Example 1: Step 1: Raw materials: weigh 3 mol of ferric phosphate, 1 mol of disodium hydrogen phosphate, 1 mol of sodium carbonate, polyethylene glycol as the dispersant, and glucose as the carbon source, all of which account for 5 wt%.

[0064] Step 2: Add the weighed raw materials in step 1 into a stirring tank filled with deionized water in sequence, stir for 1 hour until the raw materials are completely dispersed and dissolved without agglomeration, transfer to a sand mill, and perform sand milling to obtain a slurry. The slurry pH is 7, and the slurry particle size D50 is 0.15 μm.

[0065] Step 3: spray granulate the slurry in step 2 by spray drying to obtain dry precursor powder, wherein the inlet air temperature of the spray drying is 230°C; and the outlet temperature is 112°C.

[0066] Step 4: The precursor powder in step 3 is subjected to sintering reaction under the protection of inert gas, the sintering temperature is 500°C, the holding time is 6 hours, and the heating rate is 3°C / min, to obtain carbon composite sodium iron phosphate positive electrode material particles. The carbon content in the positive electrode material particles is 2.2%, wherein the inert gas is N2.

[0067] Step 5: crush and classify the composite sodium iron phosphate positive electrode material particles obtained in step 4, wherein the crushed particle size D50 is 3 μm, to obtain the final composite sodium iron phosphate positive electrode material. The powder resistivity of the positive electrode material is 550000 Ω / cm 3 ; Raman test peak area ratio I D / I G =3.3.

[0068] After assembling it into a button-type half-cell, electrochemical tests showed that the reversible gram capacity at 0.2C was 100 mAh / g, the ICE was 87%, the reversible gram capacity at 1C was 94 mAh / g, and the 1C cycle stability for 200 cycles was greater than 99%.

[0069] Comparative Example 2: Step 1: Raw materials: weigh 1.8 mol of ferric phosphate, 1.2 mol of disodium hydrogen phosphate, 0.8 mol of sodium carbonate, 0.2 mol of Ni2O3, polyethylene glycol as the dispersant, and glucose as the carbon source, all of which account for 5 wt%.

[0070] Step 2: Add the weighed raw materials in step 1 into a stirring tank filled with deionized water in sequence, stir for 1 hour until the raw materials are completely dispersed and dissolved without agglomeration, transfer to a sand mill, and perform sand milling to obtain a slurry. The slurry pH is 7, and the slurry particle size D50 is 0.15 μm.

[0071] Step 3: spray granulate the slurry in step 2 by spray drying to obtain dry precursor powder, wherein the inlet air temperature of the spray drying is 230°C; and the outlet temperature is 112°C.

[0072] Step 4: The precursor powder in step 3 is subjected to sintering reaction under the protection of inert gas, the sintering temperature is 500°C, the holding time is 6 hours, and the heating rate is 3°C / min, to obtain carbon composite sodium iron phosphate positive electrode material particles. The carbon content in the positive electrode material particles is 2.2%, wherein the inert gas is N2.

[0073] Step 5: crush and classify the composite sodium iron phosphate positive electrode material particles obtained in step 4, wherein the crushed particle size D50 is 3 μm, to obtain the final composite sodium iron phosphate positive electrode material. The powder resistivity of the positive electrode material is 5500 Ω / cm 3 ; Raman test peak area ratio I D / I G =3.1.

[0074] After assembling it into a button half-cell, electrochemical tests showed that the reversible gram capacity at 0.2C was 90mAh / g, the ICE was 89%, the reversible gram capacity at 1C was 80mAh / g, and the 1C cycle stability for 200 cycles was greater than 95%.

[0075]

[0076] In the present invention, if nickel oxide is used as a catalyst, the resistivity of the material can be effectively reduced. However, the introduction of impurity elements changes the crystal structure of the composite sodium iron phosphate, affects the stability of the material, and reduces the long-term circulation of the material, which is a deterioration effect.

[0077] The above examples are only embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing a low resistivity carbon composite phosphate sodium iron pyrophosphate positive electrode material, characterized in that The following steps are involved: Step (1): weighing an iron source, a sodium source, a phosphorus source, a dispersant, an organic carbon source, and a catalyst, wherein the iron source, the sodium source, and the phosphorus source are mixed according to the element ratio of the carbon composite sodium iron phosphate material Na4Fe3(PO4)2P2O7@C; Step (2): adding the raw materials in sequence into a stirring tank filled with deionized water, stirring until the raw materials are completely dispersed and dissolved without agglomeration, thereby obtaining a slurry; Step (3): spray granulating the slurry by spray drying to obtain a dry precursor powder; Step (4): sintering the precursor powder under the protection of an inert gas to obtain carbon composite sodium iron phosphate positive electrode material particles; Step (5): crushing and classifying the composite sodium iron phosphate positive electrode material particles to obtain a composite sodium iron phosphate positive electrode material.

2. The preparation method according to claim 1, characterized in that: In the step (1), the ratio of the dispersant to the organic carbon source is 1:1, accounting for 5% to 10% by mass; the catalyst as a part of the iron source accounts for 10% to 50% by mole of the iron source.

3. The preparation method according to claim 1, characterized in that: In the step (2), the slurry has a solid content of 10 to 60 wt%, a pH of 3 to 7, and a stirring time of 0.5 to 3 h.

4. The preparation method according to claim 1, characterized in that: In the step (3), the inlet air temperature of the spray drying is 160-250°C; and the outlet air temperature is 75-115°C.

5. The preparation method according to claim 1, characterized in that: In the step (4), the sintering temperature of the sintering reaction is 440°C to 600°C, the holding time is 3 to 10 hours, and the heating rate is 2 to 10°C / min.

6. The preparation method according to claim 1, characterized in that: In step 4, the carbon content of the positive electrode material is 1% to 3%, wherein the inert gas includes one of N2 and Ar2.

7. The preparation method according to claim 1, characterized in that: In the step (5), the crushed particle size D50 of the crushed and classified material is 1 to 5 μm; the powder resistivity of the composite sodium iron phosphate positive electrode material is 10 Ω / cm 3 ~100000Ω / cm 3 ; Graphitization degree of carbon coating layer I D / I G It is 2.0~3.

5.

8. The preparation method according to claim 1, characterized in that: The iron source includes one or more of ferric phosphate, ferrous oxalate, and ferric nitrate; The sodium source includes one or more of sodium oxalate, sodium phosphate, sodium pyrophosphate, sodium formate, sodium acetate, and sodium carbonate; The phosphorus source includes one or more of phosphoric acid, ammonium phosphate, and pyrophosphoric acid; The carbon source includes one or more of glucose, sucrose, citric acid, malic acid, phenolic resin, and gluconic acid; The dispersant includes one or more of polyethylene glycol and polyvinyl alcohol; The catalyst includes one or more of FeO, Fe2O3, Fe3O4, FeCl3, Fe(OH)3, Fe powder and the like.

9. A composite sodium iron phosphate positive electrode material, characterized in that: The method is prepared by the preparation method according to any one of claims 1 to 8.

10. A method for preparing a positive electrode sheet for a sodium ion battery, characterized in that: The steps include: Step (1): mixing the composite sodium iron phosphate positive electrode material of claim 9 with a conductive agent and an adhesive in a mass ratio of 0.95:0.25:0.25 to prepare a mixed slurry; Step (2): stirring the mixed slurry evenly, coating the mixed slurry evenly on a carbon-coated aluminum foil, and performing vacuum drying in an oven to obtain a positive electrode material for a battery; Step (3), slicing the battery positive electrode material, evenly cutting it into circular electrode sheets, and performing secondary drying on the circular electrode sheets to obtain a sodium ion battery positive electrode sheet.

11. The preparation method according to claim 10, characterized in that: The conductive agent is one or more of conductive carbon black, acetylene, carbon nanotubes, and conductive graphite; The solvent for preparing the mixed slurry is nitrogen methyl pyrrolidone.

12. The preparation method according to claim 10, characterized in that: The mixing time of the mixed slurry in step (2) is 2 hours, and the drying time is 3 hours; The secondary drying time in step (3) is 2 hours.

13. The preparation method according to claim 10, characterized in that: The diameter of the circular electrode is 14 mm, and the surface density is 15-20 mg / cm 2 .

14. A button battery, characterized in that Includes the following materials; The composite sodium iron phosphate positive electrode sheet prepared by the method as described in claims 10 to 13, the negative electrode is metallic sodium, the separator is GF / C, and the electrolyte is NaPF6 dissolved in ethylene carbonate (EC) + dimethyl carbonate (DMC).

Citation Information

Patent Citations

  • Preparation method of sodium-electrographitized carbon-coated iron phosphate positive electrode material

    CN118206091A

  • Sodium ion battery positive electrode material and application thereof

    CN118231587A

  • Carbon-coated Na4Fe3 (PO4) 2 (P2O7) positive electrode material, preparation method thereof and sodium ion battery

    CN118538902A

  • Doped ferric sodium pyrophosphate positive electrode material, preparation method and application thereof

    CN118841531A